2005
DOI: 10.1093/bja/aei219
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal side-effects of remifentanil patient-controlled analgesia in labour

Abstract: At the bolus dose used remifentanil PCA has an acceptable level of maternal side-effects and minimal effect on the neonate. Remifentanil crosses the placenta and appears to be either rapidly metabolized or redistributed in the neonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
95
3
13

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(123 citation statements)
references
References 23 publications
12
95
3
13
Order By: Relevance
“…Our regimens for remifentanil and fentanyl were based on previous studies performed at our hospital that demonstrated effective analgesia with minimal maternal adverse effects. 15,29 Although remifentanil IVPCA has been used widely in the last decade for pain management during labour with 11,13,[15][16][17][18] or without background infusion, 6,12,14,[19][20][21] its most appropriate dosing regimen is still debated. Effective analgesia has been shown in studies that used infusions and escalating dose regimens titrated to individual patient requirements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our regimens for remifentanil and fentanyl were based on previous studies performed at our hospital that demonstrated effective analgesia with minimal maternal adverse effects. 15,29 Although remifentanil IVPCA has been used widely in the last decade for pain management during labour with 11,13,[15][16][17][18] or without background infusion, 6,12,14,[19][20][21] its most appropriate dosing regimen is still debated. Effective analgesia has been shown in studies that used infusions and escalating dose regimens titrated to individual patient requirements.…”
Section: Discussionmentioning
confidence: 99%
“…10 They found differences in the maternal pain scores only during the first hour and no differences in the neonatal outcome between the three groups. To date, the literature supports the safety of remifentanil from a neonatal standpoint, 6,7,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] while several studies have shown that fentanyl PCA may be associated with neonatal depression. 1,9,[25][26][27][28] Therefore further research is needed to ensure the safety of these drugs while used for IVPCA in labouring women.…”
Section: Résumémentioning
confidence: 98%
See 1 more Smart Citation
“…Data concerning the consumption of remifentanil has been reported in 4 papers: Volikas et al (2005) and Evron et al (2008) reported a mean consumption of 0.12-0.14 μg/kg/min with IVPCA. Balcioglu et al (2005) reported a mean consumption of 0.25-0.27 µg/kg/min, while D' Onofrio et al (2009) noted the largest infusion rate used by parturients with a continuous median infusion of 0.075 µg/kg/min.…”
Section: Remifentanilmentioning
confidence: 99%
“…Volikas et al (2005) recorded hourly sedation during remifentanil analgesia on a 4-point scale (1 = alert, 2 =slightly drowsy but alert to voice, 3 = drowsy but responds to gentle stimulation, 4 = very drowsy) noting 22 out of 50 women being rated with score of 2 for ≥2h, but this was the highest recorded level of sedation. Blair et al (2001) used both subjective scoring with VAS (0-10) for sedation and observer scoring (1 = awake, 2 = drowsy, 3 = rousable to voice, who scored a sedation score of 2 (responds only after mild prodding and shaking) after a 0.5 µg/kg PCA bolus and a background infusion of 0.025 µg/kg/min.…”
Section: Sedationmentioning
confidence: 99%